The principles and practice of bar and beverage management raising the bar - Murphy, James (Oxford Goodfellow Publishers Ltd, 2013)
A comprehensive text and resource book designed to explain the latest developments in and new complexities of managing modern bars- be they stand alone or part of larger institutions such as hotels and resorts.
Preface -- Chapter 1. The pub and bar -- Chapter 2. The role of the bartender -- Chapter 3. Customer care -- Chapter 4. Responsible service of alcohol -- Chapter 5. Food and beverage equipment -- Chapter 6. Food safety and hygiene in the bar -- Chapter 7. Handling cash and payments in the bar -- Chapter 8. Sales and marketing -- Chapter 9. Safety and security in the bar -- Chapter 10. Stock and beverage control: ch11 food in the bar -- Chapter 12. Cultural diversity, intercultural awareness -- Chapter 13. Waste management -- Chapter 14. Food and beverage service procedures -- Index.
Keywords: Bars (Drinking establishments) -- Management